Implementing Continuous Improvement through Idea Management System: A Systematic Literature Review - Agung Kuncoro Budi; Pawenary Pawenary (Community Engagement and Emergence Journal (CEEJ), 2026)
The concept of continuous improvement (CI) is essential for sustaining operational excellence and fostering organizational innovation. The Idea Management System (IMS) is a structured tool that has recently gained popularity. Its purpose is to collect, evaluate, and apply employee-generated ideas inside formal improvement procedures. In this study, 14 peer-reviewed publications published between 2010 and 2024 are systematically analyzed with an emphasis on IMS implementations that enable CI in diverse organizational contexts. The role of IMS is positioned not only as a CI enabler but also as an integral component of organizational knowledge management, facilitating the capture, dissemination, and institutionalization of employee knowledge. By fostering a culture of participation, enhancing the quality of ideas, and encouraging iterative process changes, the results show that both digital and suggestion-based IMS considerably increase CI. However, there are still gaps in integrating cutting-edge technology like Artificial Intelligence (AI) and assessing long-term effects. In order to optimize the strategic value of IMS in continuous improvement programs, this study synthesizes important success criteria and suggests future research topics.